The raven scholar - Hodgson, Antonia (Hodgson, Antonia. Eternal path trilogy, 2025)
Let us fly now to the empire of Orrun, where after twenty-four years of peace, the reign of Bersun the Brusque has come to an end. In the dizzying heat of midsummer, seven exceptional warriors, thinkers, strategists compete to replace him. When one of them is murdered, it falls to Neema Kraa, the emperor's brilliant, idiosyncratic High Scholar, to find the killer and fight for the throne. Neema believes she is alone. But we are here to help; all she has to do is let us in.If she succeeds, we will win an empire. If she fails, death awaits her. But we won't let that happen.